(untitled) (Journal of Oriental Studies, 2021)
This article is devoted to one of the most understudied research topics, the peculiarities of the migration of the Uighur ethnic group from China to Kazakhstan in the 1950s, related to the repatriation policy of the USSR. The purpose of the study is to identify and characterize the main push factors that prompted the mass exodus of Uighurs from the country. Special attention was paid to the combination of different research methods in this work: oral histories obtained by interviewing, work on archival materials about migration, analysis of materials from periodicals and the use of the biographical method in historical research. As a result of the study, several reasons were identified, including the purposeful ideology and propaganda on the part of the USSR in Xinjiang, which contributed to the emergence of migration sentiments among its indigenous population, the complex and contradictory political and economic situation in China and the split in Soviet-Chinese relations. The contribution of this work is explained by its scientific and practical significance. The results of this study can be used by analysts in the further development of cause-and-effect relationships of migration processes, and can also be useful in developing educational programs and preparing lectures on the modern history of Kazakhstan.